Race and Ethnicity in Latin America How the East India Company Shaped the Modern Multinational (Edition 2) - Wade, Peter (Anthropology, Culture and Society, 2010)
For over ten years, Race and Ethnicity in Latin America has been an essential text for students studying the region. This second edition adds new material and brings the analysis up to date.Race and ethnic identities are increasingly salient in Latin America. Peter Wade examines changing perspectives on Black and Indian populations in the region, tracing similarities and differences in the way these peoples have been seen by academics and national elites. Race and ethnicity as analytical concepts are re-examined in order to assess their usefulness.This book should be the first port of call for anthropologists and sociologists studying identity in Latin America.